(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
For we picked a PIC18F452 microchip for the design and simulation of their home automation designs. Built also on PIC18F452, our sensor measures a home’s glass doors and transmit an alert and then a warmer signals to a local or regional scale. Call the police if someone attempts to destroy in. This safeguard has been implemented. It may also recognize the landlord’s identification card. Gain entrance to the house without disarming the alarm system or setting off the alarm. The access control also assigns a – anti independence. Keep a watch on the bedroom doors and there’s a potential of a break-in. The system is continually verifying the state of their house, which the landlady does not want. As a way of avoiding burglary as well as theft, the installation of a security system has gained in popularity. Embedded linux can now bring stability by observing people’s houses thanks to substantial developments in microcontroller units. We designed a surveillance system using a PIC18F452 computer that can monitoring a landlord’s windows. The idea is to design a home alarm system that utilizes series of linear switches doors.